A systematic review of publications studies on medical tourism - Masoud, Ferdosi (Medknow Publications & Media Pvt Ltd, 2013)
INTRODUCTION: Medical tourism for any study area is complex. MATERIALS AND METHODS: Using full articles from other databases, Institute for Scientific Information (ISI), Science Direct, Emerald, Oxford, Magiran, and Scientific Information Database (SID), to examine systematically published articles about medical tourism in the interval 2000-2011 paid. Articles were obtained using descriptive statistics and content analysis categories were analyzed. RESULTS: Among the 28 articles reviewed, 11 cases were a kind of research articles, three cases were case studies in Mexico, India, Hungary, Germany, and Iran, and 14 were case studies, review documents and data were passed. The main topics of study included the definition of medical tourism, medical tourists’ motivation and development of medical tourism, ethical issues in medical tourism, and impact on health and medical tourism marketing. CONCLUSION: The findings indicate the definition of medical tourism in various articles, and medical tourists are motivated. However, most studies indicate the benefits of medical tourism in developing countries and more developed countries reflect the consequences of medical tourism.